Polymorphisms of COTL1 gene identified by proteomic approach and their association with autoimmune disorders - Jin, Eun-Heui (Korean Society of Medical Biochemistry and Molecular Biology, 2009)
To select candidate genes, we attempted to comparative analysis of protein levels between rheumatoid arthritis (RA) patients and healthy controls by two-dimensional electrophoresis (2-DE) and matrix-assisted laser desorption ionization mass spectrometry (MALDI-TOF-MS). We identified 17 proteins that showed up- or down-regulated spots in RA patients. We found that coactosin-like1 (COTL1) were highly expressed in RA patients compared with healthy controls. We performed a case-control study to determine whether the COTL1 gene polymorphisms were associated with RA and systemic lupus erythematosus (SLE). The genotype frequency of c.-1124G>T and the allelic frequency of c.484G>A in RA patients, and the genotype frequency of c.484G>A in SLE patients were significantly different from healthy controls (P = 0.009, 0.027, and 0.025, respectively). We also investigated the correlation with the levels of rheumatoid factor (RF) and anti-cyclic citrullinated peptide (CCP) antibody in RA patients, and anti-nuclear antibodies (ANA) in SLE patients. The c.484G>A polymorphism in RA patients has significant association with the levels of anti-CCP antibody (P = 0.03). Our findings demonstrated that c.-1124G>T and c.484G>A polymorphisms of the COTL1 gene might be associated with the genetic susceptibility of autoimmune disorders.